Coincidence point of four completely random operators satisfying generalized weak contractive conditions - Anh, Pham The (Sarajevo Journal of Mathematics, 2024)
Contractive conditions were investigated by various authors (see, e.g [4], [9], [13], [24]). In [22], we introduced the notion of completely random operators and proved some properties of such operators. The purpose of this paper is to present some results on the existence of random coincidence points of four completely random operators satisfying generalized weak contractive conditions. Some applications to random fixed point theorems and random equations are given.